Shedding light on the use of Cu(ii)-salen complexes in the A3 coupling reaction. Issue 2 (21st November 2019) - Sampani, Stavroula I.; Zdorichenko, Victor; Danopoulou, Marianna; Leech, Matthew C.; Lam, Kevin; Abdul-Sada, Alaa; Cox, Brian; Tizzard, Graham J.; Coles, Simon J.; Tsipis, Athanassios; Kostakis, George E.
Abstract : One air stable Cu(ii )-salen complex compound enables the generation of propargylamines. Mechanistic details, scope and limitations of this protocol are presented. Abstract : One Cu(ii ) complex, {Cu(ii )L} (1S ), has been synthesised, in two high yielding steps under ambient conditions, and characterised by single-crystal X-Ray diffraction (SXRD), IR, UV-Vis, circular dichroism (CD), elemental analysis, thermogravimetric analysis (TGA) and electron spray ionization mass spectroscopy (ESI-MS). This air-stable compound enables the generation, at room temperature and in open-air, of twenty propargylamines, nine new, from secondary amines, aliphatic aldehydes and alkynes with a broad scope with yields up to 99%. Catalyst loadings can be as low as 1 mol%, while the recovered material retains its structural integrity and can be used up to 5 times without loss of its activity. Control experiments, SXRD, cyclic voltammetry and theoretical studies shed light on the mechanism revealing that the key to success is the use of phenoxido salen based ligands. These ligands orchestrate topological control permitting alkyne binding with concomitant activation of the C–H bond and simultaneously acting as a template temporarily accommodating the abstracted acetylenic proton, and continuously generating, via in situ formed radicals and a Single Electron Transfer (SET) mechanism, a transient Cu(i ) active site to facilitate this transformation. The scope and limitations of this protocol are discussed and presented.